The Democratization of Artificial Intelligence : Net Politics in the Era of Learning Algorithms - Sudmann, Andreas (2020)
The recent explosion in interest in both the democratization of data and artificial intelligence (AI) brings important questions to the fore: How democratic is AI? How to explore the political aspects of modern machine learning if many computer scientists consider AI technologies a black box fundamentally opaque to human understanding? And how does this affect questions of accountability and political agency?This timely collection discusses the complex political dimensions of internet and AI technologies, seeking to elucidate possible avenues of democratizing AI. This includes technological strategies such as an 'Explainable AI', but also the questions of political and/or critical concepts which guide the technological process of making modern AI technology more accessible as well as suitable ways of democratizing AI beyond a purely abstract understanding of transparency and accountability.